Blue Print Of Regulation Of Extra Terrestrial Vision Aid As Medical Device In India - Pandey, Nidhi; Walia, Ramanpreet; Jain, Gaurav (Journal of Neonatal Surgery, 2025)
As it is said the Eyes are gateway to one’s soul. It is one of the most important parts of human body as it plays very unique role and functions. We recognise face after seeing through eyes and memory stored. Through interactions with others, an individual develops a self-image which is mainly based on how others react to them and how they see themselves. Men (but mostly women) are judged by their appearance and their self-esteem is influenced by how others see them. The eye is an important and one of the most complex sensory organs that we humans are endowed with. The vision aid helps us in visualizing objects and also helps us in spectrum perception, colour and depth perception. Beneath all it has characteristicsthat mimics the sense organs and are pretty much similar to cameras and camcorders, and they help us see and visualise objects when light coming from outside enters them.